Segmentation-based on-demand scalable address assignment algorithm in ZigBee networks - Zhi REN; Peng-xiang LI; Yu-kun YAO; Yong HUANG (Tongxin xuebao)
Segmentation-based on-demand scalable address assignment algorithm was proposed,which segmented the 16bit address space according to a value predefined by DAAM.When a router lacks addresses,it extended its address space to a new segment.Thus,more addresses could be attained and assigned to children.Meanwhile,the present tree routing protocol was improved to suit the extended addresses.Theoretical and simulation analysis show that our algorithm outperforms DAAM and one of its present improvements in terms of the success rate of address assignment,communication overhead,etc.